The Influence of Peppermint Aromatherapy Inhalation on Morning Sickness in First Trimester Pregnant Women in Bantur Village, Malang Regency - Winanda, Shanty; Keswara, Nila Widya (Jurnal EduHealth, 2025)
Every pregnant woman will experience a process of adjusting the body to pregnancy according to the trimester stage being experienced. The first trimester causes nausea and vomiting (emesis gravidarum) in pregnant women. Nausea and vomiting usually occur in the morning (morning sickness), but some occur at night. Changes in the mother's body system during pregnancy require both physical and psychological adaptation so that it is not uncommon for mothers to experience discomfort in these changes so that prevention and treatment are needed. This study uses a quantitative research analytical type, a Quasi-experimental research design with a one group pretest-posttest approach. This research design has carried out the first observation (pretest) so that researchers can test the changes that occur after the treatment, but in this design there is no control group (comparison). the sample size used in this study used a sample of 20 pregnant women in TM I. Sampling by purposive sampling. There is a difference before and after being given peppermint aromatherapy on reducing nausea and vomiting in pregnant women in the first trimester with a p value of 0.000. There is an effect of giving peppermint aromatherapy on reducing nausea and vomiting in pregnant women in the first trimester at the Bantur Health Center, Malang Regency.